Limitaciones en el uso y apropiación de tecnologías de información y comunicación para la negociación internacional en empresas colombianas (2017)
This article establishes the main obstacles to use and appropriate information and communication technologies (ICT) for the international negotiation process. For this, a research in 380 Colombian enterprises engaged in import and / or export operations is conducted, supported in a telephone survey to identify the reasons that affect the use of ICT. Within results, it is noted that the main reason for non-use specialized ICT is the lack of knowledge about the existence of these, so a characterization of these technologies is performed, based on a literature review. It is concluded that to improve the level of use and appropriation of specialized ICT, it is required a greater divulgation about the functionality, applicability and benefits that they offer to organizations. © 2017 (Jose Alejandro Cano, Jose Jaime Baena Rojas).